P119 Dysregulated IL-23R and CD25 T cells in post -COVID-19 Rhino-Orbital Mucormycosis patients. (20th September 2022) - Rai, Gargi; Das, Shukla; Singh, Praveen Kumar; Ansari, Mohammad Ahmad; Gupta, Neelima; Sharma, Sonal; Rawat, Kanchan
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM:   Objectives: To study the IL-23R (Th17) and CD25+ (Treg) in CD4 + T cell populations in rhino-orbital mucormycosis post-COVID-19 patients and in healthy controls. Methods: The study included 20 cases of mucormycosis and 20 healthy controls. Nasal crust, collected post-surgery was subjected to KOH/culture for mycological identification. Venous blood sample (3 ml) was collected in EDTA vials from cases and controls and stained with different monoclonal antibodies such as CD3, CD4, CD25, and IL-23R for analyzing the expression of Th17 and Treg cells by flow cytometry. The assays were performed at the time of enrolment of patients and repeat blood samples were taken from each patient for staining 3 months later after treatment prescribed by Otorhinolaryngologists. Statistical analysis was done using SPSS software and the P -value ≤ .05 considered as significant. All the data are expressed as the mean ± SD. Results: All the cases were found positive by KOH and confirmed for Rhizopus arrhizus by culture. The flow cytometry analysis showed that the percentage of CD4 + IL-23R+ (Th17) cells was significantly high in patient before treatment compared to healthy controls and found to be lower post 3 months of antifungal treatment. The percentage positivity of CD4 + CD25+ (Tregs) cells was decreased in patients (before treatment) as compared to controls and after treatment groups. The percentage positivity of CD4 + CD25 + cells was significantly increased in patients after treatment. Conclusion: We observed a noticeable immune imbalance, with elevated CD4 + IL-23R Th17 and diminished CD4 + CD25 + T regulatory cells. The findings imminently indicate the mechanism of immune dysregulation involving Th17 and Treg pathways in mucormycosis and provide evidence that restoration of Th17/Treg may be considered as a therapeutic option for long-term benefit. Recovery of CD4 + CD25 + T cells after treatment indicated a favorable phenotype outcome.